الأخلاق الاجتماعية في البوذية والإسلام = (Social ethics in Buddhism and Islam) - Ahmad, Masitoh (IIUM, 2021)
The article studies about social ethics in the teaching of Islam and Buddhism. The study aims at highlighting the points of convergency and dissimilarities in social ethics in both religions. It will discuss the ethics which govern a relationship between man in his family in marriage institution, ethics related to man‘s relationship with others in social life, like ethics between man and his fellow beings at the place of work, ethics between teachers and pupils as taught by both Islam and Buddhism. The study uses a qualitative method in which the comparative and analytical methods are applied. The study concludes that despite of differences there are many similarities in ethics and social responsibilities in the teaching of Islam and Buddhism in which ethics become the central teaching of the two religions and both religions taught the importance of fulfilling the rights and responsibilities towards others in social life.